EFFECT OF SALT ACCUMULATION AND LEACHING SUCCESSION ON SOME SOIL PHYSICAL PROPERTIES IN SOME RABEAA IRRIGATION PROJECT - Salahaldeen A. Mostaffa (Mesopotamia Journal of Agriculture)
Five irrigation units have been chosen at Al-Jazera northern irrigation project in Rabeaa region (N16, N17, C1, F10, G6). Soil samples were collected from (0–20 cm) depth during two periods. The first one was on 1/4/2004 which considered as the end of salt leaching process from the soil. The second period was on 4/8/2004 which presented the accumulation and effecting of the salt on the soil. The following soil physical properties which are soil aggregates stability, bulk density, porosity, diameter of pore size distribution, saturated hydraulic conductivity, liquid and plastic limits, Casagrande soil classification (1948) and characteristics of soil moisture retention curve were studied. The results of this study showed a decreasing in the following values: mean weight diameter, porosity and saturated hydraulic conductivity, however the salinization process showed an increasing in the following values: bulk density, liquid and plastic limits and volumetric water content of the soil at different water retention. The soil samples were classified as a medium plasticity according to Casagrande classification.